2008
DOI: 10.2466/pms.107.5.99-113
|View full text |Cite
|
Sign up to set email alerts
|

Second and Foreign Language Listening: Unraveling the Construct

Abstract: Identifying the variables which contribute to second and foreign language (L2) listening ability can provide a better understanding of the listening construct. This study explored the degree to which first language (L1) listening ability, L2 proficiency, motivation and metacognition contribute to L2 listening comprehension. 115 Persian-speaking English as a Foreign Language (EFL) university students completed a motivation questionnaire, the Language Learning Motivation Orientation Scale, a listening questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In fact, L2 listening success is contingent on a minimum of three variables: linguistic, strategic and learner variables (Buck, 2001). Metacognition, as a strategic variable, contributed to the findings of studies conducted by Tafaghodtari and Vandergrift (2008) and by Cross (2011). This linguistic variable is a strong factor that contributed to L2 listening performance.…”
Section: Downloaded By [Korea University] At 03:28 27 December 2014mentioning
confidence: 86%
“…In fact, L2 listening success is contingent on a minimum of three variables: linguistic, strategic and learner variables (Buck, 2001). Metacognition, as a strategic variable, contributed to the findings of studies conducted by Tafaghodtari and Vandergrift (2008) and by Cross (2011). This linguistic variable is a strong factor that contributed to L2 listening performance.…”
Section: Downloaded By [Korea University] At 03:28 27 December 2014mentioning
confidence: 86%
“…Although the development of metacognitive awareness stays unclear, the learners' improvement in listening achievements could indicate the positive role of the bottom-up training in the practice. Previous researchers have observed that metacognition could only account for the limited variance of listening comprehension, that of 13% (Vandergrift et al, 2006), 3% (Tafaghodtari & Vandergrift, 2008), 22% (Goh & Hu, 2013). So, still, a large portion of listening variance could be explained or determined by other factors such as linguistic knowledge, memory capacity, bottom-up skills, social-affective factors and so on (Vandergrift & Goh, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…According to Graham and Macaro (2008, p. 750), the following set of listening strategies (i.e., conscious plans to manage incoming speech (Rost 2011)) are generally associated with successful listening outcomes: (1) making predictions about the likely content of a passage; (2) selectively attending to certain aspects of the passage (i.e., deciding to "listen out for" particular words or phrases or idea units); (3) monitoring and evaluating comprehension (i.e., checking that one is in fact understanding or has made the correct interpretation); and (4) using a variety of clues (linguistic, contextual and background knowledge) to infer the meaning of unknown words. There is evidence to suggest that more successful Lx listeners naturally deploy these listening strategies when faced with a listening task, while less skilled Lx listeners do not, unless they are explicitly (Cross 2010;Diaz 2015;Seo 2005) or implicitly trained to do so (Tafaghodtari and Vandergrift 2008;Vandergrift and Tafaghodtari 2010). Although these classroom interventions differed in terms of number and type of listening strategies (explicitly or implicitly) taught to Lx listeners, they all used elements of metacognition: development of the ability to recognise the mental processes involved in listening comprehension, the ability to examine the (social, cognitive and affective) factors that impede, slow down or facilitate listening, the ability to identify what contributes or hinders sound or word perception, or the ability to choose strategies that foster overall listening development and comprehension (see Vandergrift and Goh 2012).…”
Section: Introductionmentioning
confidence: 99%